Optimizing Coastal Tourism at Biru Sehati Beach, Tanjung Piayu through Development Facility - Nursyamsu, Lathifa; Murtiono, Hendro; Savana, Julfa Sindy; Willy, Willy; Laada, Arnita Fetiyani Sangadji; Belinda, Raden Indri Atika (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
Biru Sehati Beach is a coastal tourist destination located in the Kampung Tua of Tanjung Piayu. This area has a unique characteristic with a hill in the middle of its land. However, there are several natural tourism potentials that have not been developed, and existing facilities are only provided functionally and do not have added value as a tourist attraction. This study aims to determine what facilities are already available in the coastal tourist area of Kampung Tua of Tanjung Piayu and what facilities are expected and need to be provided in the future based on tourist needs. The research method used is a qualitative-descriptive method with an observational approach to collect data related to what facilities are already available and a semi-structured direct interview method to determine the needs of tourists who are not yet available. The results of the study indicate that the shaded area on the beach which is a favorite area for tourists when visiting is not yet sufficient to meet the increasing demand of tourists during peak times, there is no dedicated area for parking, and the hilly area is not yet developed. Based on the results of the study, researchers found that the number of shaded areas with the addition of trees is needed to maintain the natural impression of the beach, the construction of a dedicated parking area, and the hilly area is developed to be used as a place to relax.spot photos, andactive movement areaas an additional variation of recreational activities.